1990
DOI: 10.1093/infdis/161.5.982
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Values of Tumor Necrosis Factor/Cachectin, Interleukin-l, Interferon- , and Interferon-  in the Serum of Patients with Septic Shock

Abstract: Serum concentrations of immunoreactive tumor necrosis factor/cachectin (TNF), interleukin-1 beta (IL-1 beta), interferon-gamma (IFN gamma), and interferon-alpha (IFN alpha) were prospectively measured in 70 patients with septic shock to determine their evolution and prognostic values. In a univariate analysis, levels of TNF (P = .002) and IL-1 beta (P = .05) were associated with the patient's outcome, but not IFN alpha (P = .15) and IFN gamma (P = .26). In contrast, in a stepwise logistic regression analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
205
2
8

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(234 citation statements)
references
References 23 publications
19
205
2
8
Order By: Relevance
“…We have previously reported that this experimental protocol elevates the blood TNF-␣ concentration to ϳ500 pg/ml (12). Comparable TNF-␣ values are observed in a number of inflammatory conditions, including sepsis, neoplastic disease, burn injury, and hepatic ischemia-reperfusion injury (6,7,9,11), but levels are markedly lower than those seen in rats injected with nonlethal doses of endotoxin (18). In addition, this dose of TNF-␣ also produces peripheral insulin resistance (29) and decreases the IGF-I content in blood and muscle (12).…”
Section: Methodsmentioning
confidence: 79%
“…We have previously reported that this experimental protocol elevates the blood TNF-␣ concentration to ϳ500 pg/ml (12). Comparable TNF-␣ values are observed in a number of inflammatory conditions, including sepsis, neoplastic disease, burn injury, and hepatic ischemia-reperfusion injury (6,7,9,11), but levels are markedly lower than those seen in rats injected with nonlethal doses of endotoxin (18). In addition, this dose of TNF-␣ also produces peripheral insulin resistance (29) and decreases the IGF-I content in blood and muscle (12).…”
Section: Methodsmentioning
confidence: 79%
“…However, it is not known whether IFN-g similarly contributes to mortality in human sepsis. IFN-g levels and outcome were not correlated in adult patients with septic shock 22 and in children with meningococcal septic shock. 1 In contrast, Girardin et al reported high levels of IFN-g in children with severe meningococcal septic shock.…”
Section: Interferon Gmentioning
confidence: 88%
“…8 IL-12 also induces the production of interferon (IFN)-g by T cells and natural killer (NK)-cells. 16, 17 The plasma levels of IFN-g are increased in experimental models for sepsis [18][19][20] as well as in human sepsis, 21,22 although not consistently. 1 Recently, IL-12 was characterized as a major cytokine in the pathogenesis of gram-negative endotoxaemia in mice 16 and in primates.…”
mentioning
confidence: 99%
“…As IL-6 and TNF-α are proinflammatory cytokines elevated during the early septic hyperinflammation and are negatively correlated with the septic survival [17,18], their concentrations in serum and peritoneal fluid were measured by ELISA. 24 h after CLP or LPS, levels of IL-6 and TNF-α in serum or peritoneal fluid were significantly lower in Park7 −/− mice compared with WT mice (Figure 2A-2D).…”
Section: Park7 −/− Mice Had Greatly Reduced Secretion Of Il-6 and Tnfmentioning
confidence: 99%